Kemampuan Kolaborasi Jaringan Pemasaran dalam Meningkatkan Kinerja UKM di Kota Ternate: Marketing Network Collaboration Capability in Improving SME Performance in Ternate City - Ida Hidayanti; Fadhliah M Alhadar (Society, 2021)
This research aims to bridge the gaps in the relationship of entrepreneurial orientation to marketing performance, as some research yielded contradictory results. This research used a survey method distributing questionnaires with open and closed-ended statements to small and medium industries. Also, convenience sampling was applied with a sample size of 100 respondents from representatives of small and medium industries in the city of Ternate. The analytical method was aided with Smart PLS. The results show that the quality of social networks has no significant effect on the performance of SMEs and that the marketing network collaboration capability has no significant effect on the performance of SMEs. This implies that business operators of conventional businesses in certain areas have not reached the markets outside Ternate City by using social media, which is a remarkably effective medium.